Evaluation of Islamic Religious Education Teaching Methods and Their Function in Improving Understanding of the Concept of Tawhid - Huzaiman Hushin; Yousif Mahmadov; Markhabat Bolat; Mohammad Ahmad Bani Amer (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This research aims to evaluate Islamic Religious Education (PAI) teaching methods and their function in increasing understanding of the concept of monotheism among students. Effective teaching methods in PAI are very important to ensure that students not only master religious knowledge but are also able to internalize the values of monotheism in everyday life. This research uses a qualitative approach with data collection techniques through observation, interviews and analysis of PAI curriculum documents. The research results show that student-centered teaching methods, such as group discussions, problem solving, and contextual learning, are more effective in increasing understanding of the concept of monotheism than conventional teacher-centered methods. Challenges in implementing this teaching method include limited time, lack of training for teachers, and limited resources. Therefore, it is recommended that there be increased teacher training and the provision of adequate resources to support the use of more interactive and participatory teaching methods. Thus, PAI teaching methods can be more effective in developing a deep understanding of monotheism among students